Re-discovering identity : a study on the theme of resistance in Ghassan Kanafani's selected novels - Husain V.T., Shafeeq (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2003)
This study analyses three novels by a Palestian writer Ghassan Kanafani (1936-72) in an attempt to explore the themes of resistance. The three novels are : Men in the Sun (1963), Return to Haifa (1969) and April Anemones (1972). An explanation of the novelist's awarenes of the role of literature is enhanced by a discussion on the concept of resistance literature. The study identifies various elements that regulate the borders and scope of such a literature. Its emphasis is on scrutinizing historical, cultural and socio-political, critical and generic dimensions of the term "resistance literature" as well as its significance in the context of Palestine and in particular of Ghassan Kanafani. Views and examples of such literature developed in other parts of the world are also brought into discussion to measure the influence of it in contemporary literary scenarios. The study mainly investigates the role of literature in the struggle of Palestine and its involvement in assisting to awaken nationalistic feelings among the people. For this purpose it analyses real life situations and images of suffering projected in everyday Palestinian life and issues related to the identity of Palestinians as the people of the land. The study also searches the influence and scope of Kanafani's message and ideologies in his writing. The study basically analyses the texts of the novels and studies critically the theory of "resistance literature" to indicate how ideas related to the Palestinian identity are represented in Kanafani's novels. It focuses on the theme of resistance in each of the novels and since this approach has not ben done before, it will contribute to the existing studies on Kanafani. it explores how the tone, style and structure have been employed by the novelist to signify the circumstances of the Palestinians. the study also suggests how each novel as a whole resists the external and internal complexities of the dilemma. The study is a pioneering attempt to explore the historical importance of Kanafani's work. It clearly shows Kanafani's role as a freedom fighter, who used his novels as a vehicle to convey his message to the public. With plenty of historical references, names of real places included in the novels, Kanafani reminds the readers about the land that was inhabited by Palestinians for centuries, and their current pathetic situation in a world that is hostile. The Palestinians' effort to come out of this physical and psychological alienation and to re-discover their identity as the 'people of the land' is supported by the present thesis. The study concludes with Kanafani's assumption tht literature is not alienated from the collective resistance to te Israeli occupation. It is a literature which defines the feature of an "authentic" Palestinian culture.